Ultrasound-assisted extraction of valuable compounds from winter melon (Benincasa hispida) seeds - Sarker, Md. Zaidul Islam (Universiti Putra Malaysia, 2013)
Ultrasound-assisted extraction (UAE) was applied for the extraction of bioactive valuable compounds from winter melon (Benincasa hispida) seeds. Effects of amplitude (25-75%), temperature (40-60°C) and sonication time (20-60 min) on crude extraction yield (CEY) and radical scavenging activities (RSA, % inhibition of DPPH˙ and ABTS˙+ free radicals) of extracts were determined using complete randomised design (CRD). The results showed that the CEY and RSA of extracts significantly affected by independent variables. The maximum value of CEY (97.14±0.36 mgg-1), scavenging of DPPH˙ radicals (32.12 ± 0.38%) and scavenging of ABTS˙+ radicals (40.52±0.73%) were obtained at the combined treatment conditions of 75%, 55°C and 40 min. The UAE results obtained were compared with those achieved by using conventional Soxhlet extraction (CSE) method. It was found UAE allowed extraction at lower temperature and the extracts obtained posses higher quality compare with CSE. UAE is a promising environment friendly technique for the extraction of bioactive compounds from winter melon (Benincasa hispida) seeds.